Respostas
respondido por:
3
Explicação passo-a-passo:
Equação do primeiro grau :
- 3/4 + 1/x = 11/12
- 1/x = 11/12 - 3/4
- 1/x = (44-36)/48
- 1/x = 8/48
- 1/x = 1/6
- x = 6
Espero ter ajudado bastante!)
respondido por:
1
Resposta:
3/4+1/x=11/12
Explicação passo-a-passo:
3÷4+1÷x=11÷12,x≠0
0.75+ 1 sob x = 11 sob 12
3 sob 4 + 1 sob x = 11 sob 12
1 sob x = 11 sob 12 - 3 sob 4
1 sob x = 1 sob 6
x= 6 , x≠ 0
x=6
e isso ai
Perguntas similares
5 anos atrás
5 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás